Exercising with reserve: Evidence that the CNS regulates prolonged exercise performance - Swart, J.; Lamberts, R. P.; Lambert, M. I.; St. Clair Gibson, A.; Lambert, E. V.; Skowno, J.; Noakes, T. D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A central debate in the exercise sciences is the nature of the fatigue that determines exercise performance under different conditions. Two opposing theories are currently popular. The first holds that exercise is limited principally by metabolic changes in the exercising skeletal muscles, so-called peripheral fatigue. An opposing model [1] holds that exercise performance is regulated by the central nervous system (CNS) to ensure that homeostasis is maintained. Recently we [2, 3] and others [4] have shown that the rating of perceived exertion (RPE), a marker of "fatigue", rises as a linear function of the duration of exercise that remains. The model also predicts that agents which interfere with these central regulatory controls in the central nervous system (CNS) could enhance exercise performance by allowing the body to approach more nearly its metabolic and cardio-respiratory limits. Accordingly, the purpose of this study was to measure the effects of an amphetamine (methylphenidate) on exercise performance at a fixed rating of perceived exertion of 16. Methods: Eight elite cyclists ingested 10mg Methylphenidate in a randomized, placebo controlled cross-over trial. Results: Compared to placebo, subjects receiving methylphenidate cycled for ~ 32% longer before power output fell to 70% of the starting value. At the equivalent time at which the placebo trial terminated, subjects receiving methylphenidate had significantly higher power outputs (19%), oxygen consumptions (13%), heart rates (12%), ventilatory volumes (11%) and blood lactate concentrations (43%) although EMG activity remained unchanged. Discussion: Thus the ingestion of a centrally-acting stimulant allowed subjects to exercise for longer at higher cardiorespiratory and metabolic stress indicating the presence of a muscular reserve in the natural state. This suggests that endurance performance is not only "limited" by mechanical failure of the exercising muscles ("peripheral fatigue"). Rather performance during prolonged endurance exercise under normal conditions is highly regulated by the CNS to insure that whole body homeostasis is protected and an emergency reserve is always present.